2002
DOI: 10.1021/jp026233p
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study on the Effect of the trans Axial Ligand of B12 Cofactors on the Heterolytic Cleavage of the Co−C Bond

Abstract: Density functional theory (DFT) Becke3LYP calculations including full and restricted geometry optimizations are carried out on the complex [Co(Cor)(Benz)(CH3)]+ (Cor = corrin, Benz = benzimidazole), which is a model of B 12 cofactors, and on the products of the two possible heterolytic cleavages of the Co−C bond, [Co(Cor)(Benz)(CH3)], CH3 +, [Co(Cor)(Benz)(CH3)]2 +, and CH3 -. The thermodynamics of the heterolytic processes are found to depend very significantly on the distance of the axial ligand from the cob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
48
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 77 publications
7
48
0
Order By: Relevance
“…All geometric optimizations were made to the default tolerances of Gaussian. Previously, DFT calculations have been made [23][24][25][26][27] for R-Cbl(III) compounds; however, there had been no calculations for the one-electron reduced products, the CH 3 -Cbl(II) species. Actually, this radical anion does not appear to have much Co(II) character since the singly occupied MO (SOMO) for the doublet species is mostly a corrin ring p * MO with only a little d yz character.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…All geometric optimizations were made to the default tolerances of Gaussian. Previously, DFT calculations have been made [23][24][25][26][27] for R-Cbl(III) compounds; however, there had been no calculations for the one-electron reduced products, the CH 3 -Cbl(II) species. Actually, this radical anion does not appear to have much Co(II) character since the singly occupied MO (SOMO) for the doublet species is mostly a corrin ring p * MO with only a little d yz character.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…As discussed below, this may result in weak trans promotion effect, namely, the complex‐substrate binding affinity would be insensitive to changes in the trans ligand. A likely prominent example is the insensitivity of the homolytic bond dissociation energy of the strongly covalent but formally ionic Co(III)–alkyl bond to the properties of the trans ligand in corrinoid complexes relevant to coenzyme B12 and other systems of biochemical interest 168–170…”
Section: The Tpe Model and σ Electronic Reorganization In Heme Chemistrymentioning
confidence: 99%
“…Density functional theory (DFT) calculations provided valuable insight into the structure and catalytic properties of adenosylcobalamin [19][20][21][22]. The Co-C bond dissociation energy of coenzyme B 12 has been estimated to be about 30 kcal/mol from DFT studies [23][24][25][26][27][28][29][30][31][32][33], which is in good agreement with experimental results [34,35]. QM/MM calculations of glutamate mutase [36] and methylmalonyl-CoA mutase [37,38] showed that the bond dissociation energy of the Co-C bond in the enzymes is significantly reduced by the geometrical distortion of the coenzyme.…”
Section: Introductionmentioning
confidence: 99%